The Conflict Catalyst: IHL's Role When Climate Change Triggers Displacement - Neeralakeri, Tejashwini P; Singh, Samaira (Faculty of Law, Universitas Brawijaya, 2025)
The escalating climate crisis is profoundly reshaping global human mobility, forcing millions to abandon their homes due to both sudden-onset disasters and insidious slow-onset environmental degradation. This paper examines how international humanitarian law (IHL) and climate-induced displacement are related, particularly when armed conflict intensifies or intersects with the consequences of climate change. Despite the informal usage of the term “climate refugee,” there is a significant protection gap because the 1951 Refugee Convention does not give it a legal designation. While IHL is primarily designed to regulate armed conflict and protect its victims, this research argues that its principles and provisions become indirectly, yet crucially, relevant when climate change acts as a “threat multiplier,” intensifying existing conflicts or creating new fragilities that lead to displacement. Through a qualitative legal analysis complemented by three diverse case studies, the Sunderbans (India and Bangladesh), the Lake Chad Basin, and Somalia/Horn of Africa. The paper aims to critically analyse the applicability and limitations of International Humanitarian Law in addressing climate-induced displacement, particularly in contexts where climate change acts as a threat multiplier for armed conflict. Through a case-based legal analysis, the article seeks to demonstrate how existing legal frameworks fall short of providing adequate protection for climate-displaced persons and to situate IHL within a broader matrix of human rights, migration, and climate governance regimes.